2017
DOI: 10.7224/1537-2073.2015-006
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of Four Clinical Gait Measures in Patients with Multiple Sclerosis

Abstract: The TUG test, the DGI, the 2MWT, and the 6MWT exhibited strong psychometric properties and were found to be significant predictors of the EDSS score. Use of these tests to prospectively monitor the effects of medical and rehabilitation treatment should be considered in the comprehensive care of patients with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 31 publications
5
36
0
Order By: Relevance
“…Our results indicated that the BBS had a consistently higher correlation with the TUG and T25FW (two measures of lower extremity strength and mobility) when compared to the DGI. The DGI correlation coefficients for the TUG and T25FW were similar to those reported previously in people with MS (DGI correlation coefficients of −0.762 and −0.778, respectively) [15] and (−0.809 and −0.800) [38]. In PDDS > 2, the DGI appeared to have greater convergence with the 6MWT when compared to TUG and T25FW, a finding similar to that reported previously [38].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results indicated that the BBS had a consistently higher correlation with the TUG and T25FW (two measures of lower extremity strength and mobility) when compared to the DGI. The DGI correlation coefficients for the TUG and T25FW were similar to those reported previously in people with MS (DGI correlation coefficients of −0.762 and −0.778, respectively) [15] and (−0.809 and −0.800) [38]. In PDDS > 2, the DGI appeared to have greater convergence with the 6MWT when compared to TUG and T25FW, a finding similar to that reported previously [38].…”
Section: Discussionsupporting
confidence: 89%
“…The DGI correlation coefficients for the TUG and T25FW were similar to those reported previously in people with MS (DGI correlation coefficients of −0.762 and −0.778, respectively) [15] and (−0.809 and −0.800) [38]. In PDDS > 2, the DGI appeared to have greater convergence with the 6MWT when compared to TUG and T25FW, a finding similar to that reported previously [38]. The BBS–TUG convergence seemed to be greater than the DGI–TUG convergence; the difference was statistically significant when multiple testing was not considered as an issue.…”
Section: Discussionsupporting
confidence: 87%
“…Functional ambulation using the Dynamic Gait Index [68,[73][74][75] Static and dynamic visual acuity assessed using an Early Treatment Diabetic Retinopathy Study (EDTR S) chart with and without passive head motion (40 0 yaw rotation at 1.5 Hz) [76,77] Visual dependency assessed using the Rod and Disc test [78,79] Cognitive impairment and processing speed assessed using the Symbol Digit Modalities Test (SDMT) [80] Impact of MS on walking assessed using the 12 item self-report walking scale (MSWS-12) Version 2.0 [81] Perceived confidence in performing activities of daily living assessed using the self-report Activities-Specific Balance Confidence Scale [82] Self-reported symptoms of poor balance and increased anxiety and arousal assessed using the Vertigo Symptom Scale-Short Form [59,83] Symptoms of visually induced dizziness symptoms assessed using the self-report Situational Characteristic Questionnaire [52] Fatigue as assessed using the self-report Fatigue Scale for Motor and Cognitive functions (FSMC) [84] Symptoms of depression and anxiety assessed using the self-report Hospital Anxiety and Depression Scale (HADS) [85] Health-related quality of life using the 29-item Multiple Sclerosis Impact Scale (MSIS-29) Version 2.0 [86], a disease specific patient-reported outcome measure [87] QALYs assessed by the Multiple Sclerosis Impact Scaleeight dimensions (MSIS-8D) and the Multiple Sclerosis Impact Scale -Eight Dimensions Patient version (MSIS-8D-P) [88,89]. Both measures are based on responses to the MSIS-29, and will be used in sensitivity analyses Retrospective diary of falls over the past month for baseline measure and prospective daily falls diary over 12 weeks for assessment 2 (T14) and follow up (T26) Treatment adherence as determined by the use of patient reported diaries and reported as the percentage of completed prescribed exercises and attendance at face to face sessions User experience of the intervention will be explored through brief semi-structured face to face individual exit interviews based on an interview schedule.…”
Section: Secondary Outcome Measuresmentioning
confidence: 99%
“…In addition, the patient completed a Lower Extremity Functional Scale (LEFS) [8] with score of 13/80. Upon the patient's fourth visit, the patient performed a Timed Up and Go (TUG) Test [9], 30-Second Chair Stand Test [10], and completed an Oswestry Low Back Pain Disability Questionnaire [11]. The prognosis for this patient was fair.…”
Section: Examinationmentioning
confidence: 99%